Pengabdian Masyarakat Melalui KKN-T Klampis Ngasem: Stunting, UMKM, dan Kampung Pancasila - Kusvilanda, Maesya Mufidah; Nabilah, Shinta; Ananta, Fauzan; Sari, Rika Puspita (Informa Science, 2025)
Thematic Community Service Program (KKN-T) is one form of community service carried out by students of Universitas Dr. Soetomo with the aim of applying knowledge while providing real benefits to society. The KKN-T activities in Klampis Ngasem Village, Surabaya carried three main themes: stunting prevention, MSME development, and strengthening the values of Pancasila in society . The implementation methods included field observations, discussions with the community, and participatory activities involving local residents directly. The results of the program showed that nutritional screening for toddlers and stunting education successfully improved the community’s health literacy. The cooking demo program, in collaboration with PT Hakiki Donarta, provided new inspiration and skills in developing businesses based on simple food products. Meanwhile, the education on planting and processing butterfly pea flower tea not only introduced the benefits of local herbal plants but also instilled the values of unity and mutual cooperation in the younger generation. Overall, the KKN-T program in Klampis Ngasem had a positive impact on the community, both in terms of health, entrepreneurship, and character building. This activity also served as a learning platform for students to sharpen their social skills and sense of responsibility.